Study to the Main Effects on the Auger de-excitation Transition - Al-Asadi, F.H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
An Eigen-state expansion method is applied to the transition of the Auger de-excitation charge transfer (AD) process in the interaction between clean Cu,Al and Na surfaces and excited incident gases H and He .We use this method to describe the effective surfaces electronic structure. It’s shown that the AD efficiency is deeply influenced by the presence of the energy band for the surfaces and the potential energy stored within the excited incident atom, thus for long interaction time we use a slowly atom’s about 1KeV to scatter from metals surfaces where the electron couldn’t probe the metal band structure and Za the surface - projectile distance. Also we drive a new formula for AD interaction Matrix element